2005
DOI: 10.1002/hep.20828
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Angiogenesis Soluble Markers in Chronic Hepatitis C *

Abstract: Angiogenesis, the formation of new vessels, has been reported to play a significant pathogenic role in liver damage-associated hepatitis C virus infection. Most of our current knowledge derives from immunohistochemical studies of hepatic biopsy samples obtained from chronic hepatitis C (CHC) patients. We evaluated whether CHC is associated with elevated serum levels of angiogenesis markers and whether these are modulated by therapy. Vascular endothelial growth factor (VEGF), angiopoietin-2 (Ang-2), and soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
60
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 36 publications
4
60
0
1
Order By: Relevance
“…Also, Wada et al (2007) (19) reported that interferon alpha treatment decreased the level of Ang-2 in hepatocellular carcinoma patients although it was combined with 5-fluorouracil and concluded that this combination has anti-proliferative and anti-737 angiogenic effects, which we can say also for our combination therapy regardless the virological response; this can be powered by the fact that also, IFN-alpha has been successfully used in patients with pulmonary hemangiomatosis, (20) angioblastomas (21) and hemangioendotheliomas (22) which was via its anti-proliferative and anti-angiogenic effects by decreasing Ang-2 level. On the other hand, in our study, we found that combined therapy by IFN/RBV raised the level of serum sTie-2 from baseline levels to end of treatment levels (17.7 ± 2.1 and 31.2 ± 1.04) respectively; this finding is similar to that mentioned by Salcedo et al (17) where he found a low level of the Ang-2 inhibitor sTie-2 receptor in 36 CHC patients were comparable to the 15 healthy controls which was markedly increased after combination therapy by IFN/RBV. However, in our study, serum Ang-2 and sTie-2 didn't express statistically significant change between responders and non-responders at 48 weeks, while Salcedo et al (17) demonstrated a close relationship between variations in serum levels of angiogenesis markers and response to therapy in CHC patients; this may be due to the smaller number of their patients or differences in samples.…”
Section: Discussion:-supporting
confidence: 93%
See 3 more Smart Citations
“…Also, Wada et al (2007) (19) reported that interferon alpha treatment decreased the level of Ang-2 in hepatocellular carcinoma patients although it was combined with 5-fluorouracil and concluded that this combination has anti-proliferative and anti-737 angiogenic effects, which we can say also for our combination therapy regardless the virological response; this can be powered by the fact that also, IFN-alpha has been successfully used in patients with pulmonary hemangiomatosis, (20) angioblastomas (21) and hemangioendotheliomas (22) which was via its anti-proliferative and anti-angiogenic effects by decreasing Ang-2 level. On the other hand, in our study, we found that combined therapy by IFN/RBV raised the level of serum sTie-2 from baseline levels to end of treatment levels (17.7 ± 2.1 and 31.2 ± 1.04) respectively; this finding is similar to that mentioned by Salcedo et al (17) where he found a low level of the Ang-2 inhibitor sTie-2 receptor in 36 CHC patients were comparable to the 15 healthy controls which was markedly increased after combination therapy by IFN/RBV. However, in our study, serum Ang-2 and sTie-2 didn't express statistically significant change between responders and non-responders at 48 weeks, while Salcedo et al (17) demonstrated a close relationship between variations in serum levels of angiogenesis markers and response to therapy in CHC patients; this may be due to the smaller number of their patients or differences in samples.…”
Section: Discussion:-supporting
confidence: 93%
“…On the other hand, in our study, we found that combined therapy by IFN/RBV raised the level of serum sTie-2 from baseline levels to end of treatment levels (17.7 ± 2.1 and 31.2 ± 1.04) respectively; this finding is similar to that mentioned by Salcedo et al (17) where he found a low level of the Ang-2 inhibitor sTie-2 receptor in 36 CHC patients were comparable to the 15 healthy controls which was markedly increased after combination therapy by IFN/RBV. However, in our study, serum Ang-2 and sTie-2 didn't express statistically significant change between responders and non-responders at 48 weeks, while Salcedo et al (17) demonstrated a close relationship between variations in serum levels of angiogenesis markers and response to therapy in CHC patients; this may be due to the smaller number of their patients or differences in samples. As regards the relation between the angiogenic factors and viremia, we found that high level of viremia was associated with increased serum levels of Ang-2 and is inversely related to level of sTie-2 Vice versa; while in a study conducted by Helaly and Abou Shamaa (23) who studied the Influence of hepatitis C virus infection on circulating levels of VEGF (another angiogenic factor similar in action to Ang-2) in patients with hepatitis C and hepatocellular carcinoma (HCC), they found a weak correlation between the level of viremia and VEGF.…”
Section: Discussion:-supporting
confidence: 93%
See 2 more Smart Citations
“…The association between hepatic inflammation and angiogenesis is not unique to NAFLD. In persons with chronic hepatitis C, serum levels of proangiogenic markers, VEGF and angiopoietin-2, were elevated at baseline and decreased after interferon-based therapy [14].…”
mentioning
confidence: 98%